STRATEGI PEMBELAJARAN INOVATIF DAN KREATIF MELALUI MEDIA CANVA PADA SISWA SEKOLAH DASAR-LITERATUR RIVIEW - Rohmah Khasanah; Sumarno; Ida Dwijayanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Education in the present era is education in the 21st century. Learning must be able to develop critical thinking and problem-solving skills, creativity and innovation, communication, and collaboration. Therefore, teachers must be innovative and creative in creating lessons that foster high-level thinking in students. One way is through the selection of varied and digitally-based learning media in accordance with the development of education. The aim of this study is to describe innovative and creative digital-based learning media, specifically using the Canva application in teaching. Lessons using the Canva application are one of the appropriate solutions to support teachers in developing digital-based learning media. The method used in this research is literature review, based on journals, books, and related articles. The researcher collected seven articles related to learning through the Canva media with a publication period ranging from 2020 to 2023. The results of this study indicate that learning using the Canva application is one of the innovative, creative, engaging, and enjoyable learning media in line with the current digital-based education development. The goal of this research is to enhance innovative, creative learning through the Canva media so that students feel happy and engaged in the learning process.